Attenuation of Cerebral Venous Contrast in Susceptibility-Weighted Imaging of Spontaneously Breathing Pediatric Patients Sedated with Propofol - Sedlacik, J.; Löbel, U.; Kocak, M.; Loeffler, R.B.; Reichenbach, J.R.; Broniscer, A.; Patay, Z.; Hillenbrand, C.M. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: SWI is known for its detailed visualization of the cerebral venous system and seems to be a promising tool for early detection of cerebrovascular pathologies in children, who are frequently sedated for MR imaging. Because sedation influences cerebral hemodynamics, we hypothesized that it would affect cerebral venous contrast in SWI. MATERIALS AND METHODS: SWI (125 examinations) of 26 patients (age, 2–16 years) was reviewed in this study. Images were acquired of patients sedated with propofol. Reviewers classified the images by weak or strong venous contrast. Physiologic data, such as etCO2, BP, age, and CBF by arterial spin-labeling, were monitored and collected during MR imaging. A generalized estimating equation approach was used to model associations of these parameters with venous contrast. RESULTS: EtCO2 and CBF were found to correlate with venous contrast, suggesting that patients with high etCO2 and CBF have weak contrast and patients with low etCO2 and CBF have strong contrast. BP was also found to correlate with the venous contrast of SWI, suggesting that patients with high BP have strong venous contrast. No significant correlations were found for any other physiologic parameters. CONCLUSIONS: We found that the venous contrast in SWI is affected by propofol sedation in spontaneously breathing patients. We also found that low etCO2, low CBF, and high BP are associated with strong venous contrast. Reviewing SWI data in light of physiologic measures may therefore help prevent potential misinterpretations of weak venous contrast in SWI examinations under propofol sedation. ASLarterial spin-labelingBOLDblood oxygenation level–dependentBPblood pressureCBFcerebral blood flowetCO2end-tidal carbon dioxideFAflip angleGEEgeneralized estimating equationsPETpositron-emission tomographyQ2TIPSquantitative imaging of perfusion using single subtraction, second version, with thin-section TI1 periodic saturationRBCred blood cell countRRrespiration rateSWIsusceptibility-weighted imaging